What are the priorities for prevention and control of non-communicable diseases and injuries in sub-Saharan Africa and South East Asia? (2012)
Last year’s UN high level meeting sought to galvanise the international community into scaling up its response to the escalating global burden of non-communicable diseases. With resources tight, D Chisholm and colleagues examine which interventions should be given priority for action and investment